Numerical Simulation of Aircraft Icing with an Unsteady Thermodynamic Model considering the Development of Water Film and Ice Layer - Xiaobin Shen; Zicheng Qi; Wenzhao Zhao; Guiping Lin; Yu Zeng; Zuodong Mu (International Journal of Aerospace Engineering)
Considering the transient heat and mass transfer process of the impinged water droplets during aircraft icing, an unsteady thermodynamic model was established to simulate the dynamic developments of the water film and the ice layer on aircraft surfaces. The unsteady model was discretized in an implicit scheme with a corresponding solution method. Icing simulations were performed for a NACA0012 airfoil, and the results show acceptable agreement with the data in the literature. Water film first appears near the stagnation point, and then, the film thickness increases, and the runback water region expands with time, affecting the icing rate, the surface temperature, and the ice type. The development of the water film is rapid, and the thickness and range of the film, along with the icing rate, reach a steady state in a short time. The stable characteristics obtained by the unsteady model are consistent with those of the Messinger steady model. Despite that the unsteady and steady models can obtain similar ice shapes in icing simulations, the dynamic developments of the water film and the ice layer should be considered at the initial stage of ice accretion or in the short-time icing simulations.